Administrative And Medical Documentation Efficiency, Nursing, Physiotherapy, And Laboratory Practices And Their Influence On Patient Safety In Internal Medicine Units (The Review of Diabetic Studies, 2024)
Patient safety within internal medicine units is a paramount concern, critically dependent on the seamless interplay between information systems and clinical execution. This research investigates the multifaceted relationship between the efficiency of administrative and medical documentation systems and the core practices of nursing, physiotherapy, and laboratory services, assessing their collective influence on patient safety outcomes. Utilizing a mixed-methods approach, the study identifies significant vulnerabilities at the intersection of these elements. Findings reveal that inefficient documentation creates substantial burdens, leading to cognitive overload, delayed communication, and increased reliance on error-prone workarounds. Specifically, nursing clinical vigilance is compromised by documentation tasks, physiotherapy safety recommendations are often lost in interdisciplinary gaps, and laboratory informatics failures impede diagnostic timeliness. These disconnected workflows foster an environment where preventable adverse events, such as medication errors, falls, and delayed diagnoses, are more likely to occur. The study concludes that isolated improvements within single domains are insufficient. Instead, it advocates for the adoption of an Integrated Safety Model, underpinned by human-centered health IT design, intelligent clinical decision support, standardized communication protocols, and a culture of shared accountability. By strategically aligning documentation efficiency with clinical workflows, healthcare systems can transform their information ecosystem into a proactive, resilient foundation for patient safety.